Meaning-Focused Interaction Model Based on Natural Language Acquisition Principles for Speaking Learning in BIPA - Ananda Siti Khoirunnisa; Vismaia S. Damaianti; Yeti Mulyati (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
BIPA 2 learners may have difficulty understanding words, phrases, or oral expressions that are often used by native speakers in conversation. This study aims to produce a meaning-focused interaction model based on the principle of natural language acquisition in BIPA 2 speaking learning. The research method used is Research and Development (R&D) with a 4D research design. The data in this study came from 2 expert validators, 3 practitioners, and 21 BIPA learners. The methods used in collecting data were interviews, observations, questionnaires, and tests. Data analysis was carried out using quantitative and qualitative analysis. The results of the study were that expert validators assessed with a very feasible category for model design (97.61%), media (92%), and learning evaluation (97.7%). The model product was tested under intervention conditions in a speaking class with the topic of 'Holidays.' The trend of changes in the graphs of the four dominant learners increased, proving an increase in their speaking abilities. BIPA teachers responded to the feasibility of the model product with a percentage of 93.3%, and learners 100%. This model has been proven to be able to improve learners' speaking abilities and accommodate the needs of interactive speaking class situations. The research implies that the use of this model can help BIPA teachers to apply learning models in speaking classes.